Metal-organic frameworks-loaded indocyanine green for enhanced phototherapy: a comprehensive review - Zou, Yutao; Zhang, Qiuyun; Chen, Jiayi; Wang, Weiqi; Zheng, Xiaohua (Frontiers in Bioengineering and Biotechnology, 2025)
Indocyanine green (ICG) is a small molecule approved by the U.S. Food and Drug Administration (FDA) for liver function imaging and angiography. ICG can be used not only for near-infrared imaging but also for photodynamic and photothermal therapy. However, the hydrophilicity of ICG leads to a relatively short blood circulation time, and it is easily cleared by organs such as the liver. Moreover, it lacks the targeting ability to the diseased sites. By using the natural porous metal-organic frameworks (MOFs) as the carrier, high-efficiency loading of ICG molecule can be achieved, which has significantly broadened its biomedical applications. This review comprehensively summarizes the research work in recent years regarding the utilization of MOF as a carrier to load ICG in the bioapplication such as malignant cancer inhibition, antibacterial treatment, and the treatment of Alzheimer’s disease. It focuses on summarizing the design concepts of different types of MOF carriers for loading ICG molecules. Meanwhile, it emphasizes the enhanced therapeutic effects achieved when multiple treatment modalities realized through post-modification are combined with ICG-mediated phototherapy. It is expected that through the summary of this review, the biomedical applications of ICG in the field of disease treatment can be further promoted.